2014
DOI: 10.1103/physreve.90.052703
|View full text |Cite
|
Sign up to set email alerts
|

Generation of stationary and moving vortices in active polar fluids in the planar Taylor-Couette geometry

Abstract: We study the dynamics of an active polar fluid in the interstitial space between two fixed coaxial cylinders. For sufficiently large expansive or contractive active stresses, the fluid presents roll instabilities of axially symmetric states leading to the spontaneous formation of vortices in the flow field. These vortices are either stationary or travel around the inner cylinder. Increasing the activity further, our numerical solutions indicate the existence of active turbulence that coexists with regular vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…Some continuum models of active matter in confinement have previously predicted unidirectional flow or net circulation [21][22][23][24][25]. Ravnik et al [24] found that the bacterial flow in a pipe has a weak (~1%) component along the y and z directions, but with vortex patterns quite different from the wave-like stream we observe here.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Some continuum models of active matter in confinement have previously predicted unidirectional flow or net circulation [21][22][23][24][25]. Ravnik et al [24] found that the bacterial flow in a pipe has a weak (~1%) component along the y and z directions, but with vortex patterns quite different from the wave-like stream we observe here.…”
Section: Discussionsupporting
confidence: 46%
“…Using discrete [19], continuum [20], and phenomenological models, this growing field of research has studied self-organisation of populations of interacting motile organisms or other kinds of active and driven objects, often giving rise to striking collective behaviours. Recent studies have predicted that physical confinement can have a strong impact on the spatio-temporal organization, and indeed may result in unidirectional flows [21][22][23][24][25][26]. Experimental realisations of confined active matter however remain relatively rare [14][15][16][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Continuum theories of active nematics also demonstrate the possibility of stabilising active turbulence in circular or cylindrical confinement [18,[20][21][22][23][24][25]. These calculations emphasise the role of topological defects in controlling the flow.…”
Section: Circular Confinementmentioning
confidence: 80%
“…The resulting torque-rotational velocity relation can display regions with multiple unstable branches and the coexistence of states with rotations in the opposite direction. For higher activities, secondary instabilities have been reported that lead to the emergence of topological point defects and possibly chaotic behavior (Neef and Kruse, 2014), Fig. 15(b), which has been observed in extensile active nematics (Sanchez et al, 2012), Fig.…”
Section: Hydrodynamics Of Motor-filament Networkmentioning
confidence: 96%
“…Arrows indicate the flow, colours the orientation angle ψ of the polarization field with respect to the radial direction. From (Neef and Kruse, 2014). (c) Spontaneous flow field (arrows) in a reconstituted system of microtubules and motor complexes.…”
Section: Hydrodynamics Of Motor-filament Networkmentioning
confidence: 99%